Carcass and meat quality of crossbreds of Thai indigenous chickens and Rhode Island Red layer chickens as compared with the purebreds and with broilers - C. Kaewkot (2020)
© 2020 CSIRO. Context: In order to maintain the availability of meat from indigenous chicken types in remote Asian regions with their special meat quality, novel ways of increasing efficiency are needed. One way could consist of crossbreeding with layer type chickens that are genetically quite distant from indigenous breeds. Aim: The three hypotheses tested were as follows: that the meat quality of indigenous chickens differs from that of broilers; that the meat quality of male layer chickens resembles that of indigenous chickens rather than that of broilers; and that crossbreds of indigenous chickens and layer types overall are superior to the respective purebreds. Methods: We studied carcass and meat quality of crossbreds of Thai indigenous Pradu Hang Dam (PD) and Rhode Island Red (RR) layers, and compared them with the corresponding purebreds and a commercial broiler type (Ross) in a complete randomised design. Chickens were reared in 4 × 5 pens with 10 chickens each for 120 days (Ross: 45 days). Key results: The crossbreds were superior to PD and RR in body and carcass weight, as well as breast meat percentage, but in Ross the latter was 1.7 times higher. The Ross meat was lighter, more yellow and less red and had a higher intramuscular fat content and drip loss and a lower thawing loss and shear force than that of the three other types. Nucleotide content was either similar in all chicken types or lower in Ross meat. Ross meat was more susceptible to lipid oxidation than that of the three other types although the Ross muscles lipids contained less polyunsaturated fatty acids. Conclusion: Considering the better carcass yield and breast meat proportion, crossbreeding of indigenous chickens with a layer breed likely is be economically advantageous. Implications: Overall, fattening of crossbreds turned out to be a valid alternative to improve fattening systems and to preserve the specific meat quality of indigenous chickens.